(untitled) (Bulletin of Innovative Research, 2026)
This article presents a comparative-philosophical analysis of the concept of harmony in the musical philosophy of Abu Nasr al-Farabi and its theoretical relationship with the ideas of Plato and Aristotle. The study identifies the ontological, aesthetic, psychological, and ethical dimensions of the category of harmony and demonstrates its multi-layered and integrative character in al-Farabi’s doctrine. Furthermore, it is shown that al-Farabi creatively reinterpreted the Greek philosophical heritage, understanding music as a unified system of mathematical proportions, spiritual balance, and social perfection. The findings of this research allow al-Farabi’s musical philosophy to be considered as a theoretical bridge between the intellectual traditions of the East and the West.